2017
DOI: 10.5114/ada.2017.65618
|View full text |Cite
|
Sign up to set email alerts
|

A study of dermoscopic features of nail psoriasis

Abstract: IntroductionDermoscopy is a non-invasive imaging method that enables the evaluation of pigmented and non-pigmented skin lesions. More recently, dermoscopy has been recognized as an effective tool in the diagnosis of nail diseases.AimTo evaluate the dermoscopic features of nail psoriasis and to assess the relationship between these features and disease severity.Material and methodsA total of 67 patients with clinically evident nail psoriasis (14 women, 53 men) were prospectively enrolled. Following a thorough c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
73
1
23

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(124 citation statements)
references
References 22 publications
12
73
1
23
Order By: Relevance
“…The frequency of onychoscopic features was analysed in two studies, including 68 and 67 patients, respectively. 41,42 In the study by Yadav et al 41 , subclinical onychoscopic changes were found in 46 of 68 patients with psoriasis vulgaris. Coarse pits/pitting constituted the most common onychoscopic feature indicating nail matrix involvement, while the most common onychoscopic feature indicating nail bed involvement was splinter haemorrhages.…”
Section: Onychoscopy Of Nail Psoriasismentioning
confidence: 94%
See 1 more Smart Citation
“…The frequency of onychoscopic features was analysed in two studies, including 68 and 67 patients, respectively. 41,42 In the study by Yadav et al 41 , subclinical onychoscopic changes were found in 46 of 68 patients with psoriasis vulgaris. Coarse pits/pitting constituted the most common onychoscopic feature indicating nail matrix involvement, while the most common onychoscopic feature indicating nail bed involvement was splinter haemorrhages.…”
Section: Onychoscopy Of Nail Psoriasismentioning
confidence: 94%
“…Coarse pits/pitting constituted the most common onychoscopic feature indicating nail matrix involvement, while the most common onychoscopic feature indicating nail bed involvement was splinter haemorrhages. 41,42 Detailed data on onychoscopy in nail psoriasis are shown 43,44 Capillaries of the hyponychium described by Iorizzo et al 45 were visible in all digits and were described as dilated, tortuous, elongated and irregularly distributed. Capillary density correlated positively with disease severity.…”
Section: Onychoscopy Of Nail Psoriasismentioning
confidence: 99%
“…In our opinion, red and black filamentous structures, that we detected on dermoscopy, correspond to subungual capillary remnants of this complex microvasculature. In a recent study, it has been demonstrated that identical dermoscopic features are found in nail bed psoriasis [11]. Nail psoriasis is characterized by increased hyponychial capillary density.…”
Section: Casementioning
confidence: 96%
“…Nail psoriasis is characterized by increased hyponychial capillary density. Dilated, tortuous hyponychial capillaries are found in psoriatic patients [11,12]. Traumatic onycholysis is another nail disorder, in which damaged capillaries are exposed in the hyponychial area.…”
Section: Casementioning
confidence: 99%
“…2 Of note, the usefulness of dermoscopy in recognizing ACH is further emphasized by the fact that similar conditions entering into the differential diagnosis typically show different dermoscopic features, including: (i) onychomycosis, commonly featuring chromonychia, onycholysis having a jagged proximal edge with spikes, opacity and longitudinal striae; 3 (ii) nail lichen planus, which is mainly characterized by chromonychia, trachyonychia, nail plate fragmentation and longitudinal streaks; 4 (iii) acral hand eczema, classically showing yellowish scales, brownish-orange dots/globules and yellowishorange crusts; 2 and (iv) psoriatic onychopathy, which frequently displays distal splinter hemorrhages, pits surrounded by a peripheral whitish halo and distal onycholysis encircled by an erythematous border. 5 In conclusion, dermoscopy may help highlight the typical pustules of ACH, even when they are scarcely visible on clinical grounds, thereby increasing the index of suspicion for such a condition. This may particularly come in handy for clinicians who are not very familiar with this rare disease, thus potentially reducing diagnostic mistakes/delays which may have a relevant impact on possible long-term destructive sequelae.…”
mentioning
confidence: 96%